PRESERVATION AND SUPPORT FOR THE HEALTH CARE WISDOM OF THE ELDERLY IN NORTHEASTERN REGION OF THAILAND - Krairach, D (PEOPLE: International Journal of Social Sciences, 2017)
This research was a qualitative research. The purposes were to find the health care wisdom of the elderly in the northeastern region (Esan) of Thailand, and to develop the potential of teaching the wisdom of the elderly in the northeastern region of Thailand. The study area was Ban Pho Community, Mahasarakham Province.One hundred twenty persons of the informant group were the elderly with wisdom, students, teachers and persons from the general public in the community. Data collection employed participatoryobservation method, in-depth interview, group discussion and synthesis. Analysis and interpretation of data employed inductive and interdisciplinary methods. The duration of research was one year. The result revealed that most of the elderly people had at least 1-2 health care wisdoms, such as wisdom in Herbal Plants and Vegetablesfor health care, local cuisine and confectionery from vegetable and natural ingredients and without toxics and chemicals, making local confectionery, traditional massage, bamboo wickerwork,playing folk music. The researchers developed the elderly in teaching skills, use the Buddhist principle and led the elderly to transfer knowledge to their descendants at elementary schools and the community. After one academic year, the students began to see the value of the elderly different from the past, that they thought "old people are not worth much, they are just waiting to die," as well as have a better understanding about the value of folk wisdom than in the past that they were interested about only technologies and modern things, but now they have intention to preserve the wisdom and making it sustainable for the community.